Bintaro Leaves (Cerbera manghas): Toxicity to Aedes aegypti Instar III Larvas - Sasmitasari, Nur Ilmi Dwi; Permana, Tutut Indria; Susetyarini, Eko; Nuryady, Moh. Mirza; Dinindra, Anka Muhammad; Agustin, Jihan Ully; Lutfi, Muhammad Ahman; Ayu, Putri; Alimatul, Zada (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
DHF cases tend to increase from year to year in Indonesia. So the government makes efforts to control cases of Dengue Fever (DHF) which are usually done chemically and harm the environment and health. There is a need for safer, more effective, and environmentally friendly controls, such as using natural ingredients as natural larvicides. Among the natural ingredients having potential as a larvicide is Bintaro leaves (Cerbera manghas). The purpose of this study was to determine the toxicity of Bintaro leaf extract against third instar larvae of Aedes aegypti mosquitoes. This experimental study used 7 treatments of Bintaro leaf extract concentration (5 %, 15 %, 25 %, 35 %, 45 %, 65 %, 75 %), abate as a positive control, and distilled water as a negative control. Each treatment used ten instar III Aedes aegypti larvae with four repetitions. The data obtained were then analyzed using probit analysis to determine the toxicity of Bintaro leaf extract to Aedes aegypti larvae by calculating the LC50 and LC90 values. The results showed that the most effective concentration was 75 % because it could kill 100% of the test larvae. The LC50 value of 5,097 % and the LC90 value of 25,300 % indicate that the level of toxicity is very toxic. The probit regression analysis shows a linearity line equation y = 1.15 + 1.43x with a correlation (R2) of 0.512 which indicates that the correlation is strong enough. It is related to the content of flavonoids, tannins, saponins, triterpenoids which are toxic to the abdomen, nervous system, and respiratory system of larvae. From the research results, Bintaro extract with a concentration of 75 % can be used as a natural larvicide candidate. Furthermore, further research to see the toxicity to the environment can be done.are toxic to the abdomen, nervous system, and respiratory system of larvae. From the research results, Bintaro extract with a concentration of 75 % can be used as a natural larvicide candidate. Furthermore, further research to see the toxicity to the environment can be done.